2005
DOI: 10.1089/jir.2005.25.384
|View full text |Cite
|
Sign up to set email alerts
|

Beta2-Adrenergic Receptors Mediate the Differential Effects of Catecholamines on Cytokine Production of PBMC

Abstract: We determined characteristics of beta2-adrenergic receptors (beta2R) on peripheral blood mononuclear cells (PBMC) and cytokine production after mitogenic stimulation and coincubation with catecholamines. PBMCs were stimulated with interleukin-2 (IL-2), tetanus toxoid (TT), anti-CD3 antibody, or phytohemagglutinin (PHA). The cytokines interferon-gamma (IFN-gamma), IL-4, and IL-6 were determined by ELISA following coincubation with high-dose (10(-5) M) and low-dose (10(-9) M) epinephrine (EPI) and norepinephrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 57 publications
4
33
0
Order By: Relevance
“…Substantial evidence in animals has found that sympathetic effector mechanisms suppress proinflammatory cytokine expression (12,21,38). Together, with these studies, the findings from the current study linking sympathovagal balance and IL-6 production in women suggest that the autonomic activity plays a role in modulating inflammatory cytokine expression.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Substantial evidence in animals has found that sympathetic effector mechanisms suppress proinflammatory cytokine expression (12,21,38). Together, with these studies, the findings from the current study linking sympathovagal balance and IL-6 production in women suggest that the autonomic activity plays a role in modulating inflammatory cytokine expression.…”
Section: Discussionsupporting
confidence: 75%
“…Increases in sympathetic activity along with ␤-adrenergic receptor activation suppress stimulated production of proinflammatory cytokines (12,21,38). Substantial evidence indicates that autonomic nervous system activity differs between men and women, in which men show higher levels of sympathetic balance than women (3,19,22,35).…”
mentioning
confidence: 99%
“…Although sympathetic activation has been associated with reduced stimulated production of proinflammatory cytokines (Watkins, et al, 1999), this is not always the case. For example, evidence suggests that beta-adrenergic receptor density mediates the effects of catecholamines on cytokine production (Wahle, et al, 2005) with norepinephrine inducing cytokine production in mononuclear cells exhibiting lower betaadrenergic receptor density. Those findings led us to hypothesize that stress-induced adrenergic activity, in the presence of down-regulated beta-receptors, leads to C3 production via activation of transcription factors and proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs), specifically monocytes, B cells and CD8 + T cells, from RA patients express lower levels of β2-ARs compared with healthy subjects (25) and the receptor density on RA synovial fluid lymphocytes is even less (26). RA PBMCs therefore also are less responsive to NE treatment compared with healthy subjects: upon NE administration in vitro (25,27) they are less effective in suppressing T-cell activation and proliferation, and the stimulated cytokine response was not decreased as much. In active systemic and polyarticular juvenile RA there is a diminished cAMP production upon β2-AR stimulation, indicating a defective neuroimmune response (28).…”
Section: β2-adrenergic Receptor Expression and Function In Rheumatoidmentioning
confidence: 99%